IMPROVING THE QUALITY OF EDUCATION IN THE NEW UZBEKISTAN – THE FOUNDATION OF THE THIRD RENAISSANCE (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
In this article, the idea that the most important priority for the development of the new Uzbekistan is to improve the quality of education and to raise a generation with intellectual potential, as well as the importance of the "Foundation of the Third Renaissance" for our country and its development, are discussed. the idea of its creation is directly linked to and illuminated by thoughts on the fundamental reform of the science and education system.